A different kind of hedgehog pathway: tinea manus due to Trichophyton erinacei transmitted by an African pygmy hedgehog (Atelerix albiventris). Issue 2 (25th July 2013) - Weishaupt, Julia; Kolb‐Mäurer, Annette; Lempert, Sigrid; Nenoff, Pietro; Uhrlaß, Silke; Hamm, Henning; Goebeler, Matthias
Summary The unusual case of a 29‐year‐old woman with tinea manus caused by infection due to Trichophyton erinacei is described. The patient presented with marked erosive inflammation of the entire fifth finger of her right hand. Mycological and genomic diagnostics resulted in identification of T. erinacei as the responsible pathogen, which had been transmitted by a domestic African pygmy hedgehog, Atelerix albiventris. Upon prolonged treatment with topical and systemic antifungal agents skin lesions slowly resolved. This case illustrates that the increasingly popular keeping of extraordinary pets such as hedgehogs may bear the risk of infections with uncommon dermatophytes.